2019
DOI: 10.1038/s41598-019-41400-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined Raman and polarization sensitive holographic imaging for a multimodal label-free assessment of human sperm function

Abstract: Raman microspectroscopy (RM) and polarization sensitive digital holographic imaging (PSDHI) are valuable analytical tools in biological and medical research, allowing the detection of both biochemical and morphological variations of the sample without labels or long sample preparation. Here, using this multi-modal approach we analyze in vitro human sperm capacitation and the acrosome reaction induced by heparin. The multimodal microscopy provides morphofunctional information that can assess the sperms ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…When using two orthogonally polarized reference waves, it possible to reconstruct not only morphology information but also intrinsic information about the polarization state of the sample through the phase change quantification [ 60 ]. Indeed, it has been observed that cells/tissues are composed of regularly arranged protein filaments that may affect their birefringence behavior [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…When using two orthogonally polarized reference waves, it possible to reconstruct not only morphology information but also intrinsic information about the polarization state of the sample through the phase change quantification [ 60 ]. Indeed, it has been observed that cells/tissues are composed of regularly arranged protein filaments that may affect their birefringence behavior [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the last decade, there have been significant developments in the instrumentations of QPI. [2,7,[11][12][13][14][15][16][17] For example, the spatial and temporal resolution of QPI had been improved and reached the limitations of farfield diffraction resolution and the speed of a high-speed image sensor. [18][19][20][21][22] Recently, many researchers have intensively reported biological applications of QPI, in particular, medical applications.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Cells of both H5 and H7 contain pigments, such as retinal proteins cruxrhodpsin-2 and bacterial rhodopsin. Additionally, all halophilic archaea (H1–H7) have an apparent significant Raman band at around 893 cm –1 which can be assigned to glycoproteins. , Halophilic archaea usually accumulate large amounts of monosaccharides, glycerol, and other small molecule polarizers in cells, which are used to constitute penetration regulators rapidly …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, all halophilic archaea (H1−H7) have an apparent significant Raman band at around 893 cm −1 which can be assigned to glycoproteins. 34,35 Halophilic archaea usually accumulate large amounts of monosaccharides, glycerol, and other small molecule polarizers in cells, which are used to constitute penetration regulators rapidly. 36 The SCRS of SCM1 show a distinct Raman band at 1044 cm −1 (Figure 1), which is contributed by the γ1 symmetric stretch in sodium bicarbonate.…”
Section: ■ Experimental Sectionmentioning
confidence: 97%